Advancements in Pathogen Detection: Argonaute-Based Nucleic Acid Detection Technology - Meng Hong; Guodi Wu; Yanli Ren; Shanshan Wu; Haihong Zhu; Zhi Chen (Pathogens, 2025)
In recent years, global public health security has encountered significant challenges, with infectious diseases accounting for approximately 25% of global mortality annually. The worldwide pandemic instigated by the novel coronavirus, alongside the persistent threats posed by Ebola, influenza, and multidrug-resistant bacteria, has severely compromised human health, economic development, and social stability. Within this context, the development of rapid and precise pathogen detection technologies has emerged as a critical frontline defense for epidemic prevention and control, serving as a pivotal component in the implementation of the “early detection, early isolation, and early treatment” strategy. The Argonaute (Ago) protein, recognized as a programmable and target-specific activated nuclease, has demonstrated substantial potential in the realm of nucleic acid detection due to its distinctive biological properties, garnering considerable attention. In this study, we delineate the structural characteristics of Ago proteins and elucidate the mechanism underlying their nuclease activity. Furthermore, we review the principles of nucleic acid detection based on Argonaute and provide a comprehensive analysis of recent advancements in related detection systems. Additionally, we compare the advantages of detection based on Argonaute with other detection methodologies. Through a comprehensive analysis, we aim to provide a robust theoretical foundation and an advanced technical reference for the development of new-generation nucleic acid detection platforms with high sensitivity and high specificity.